Pengaruh Waktu Heat Treatment Terhadap Karakteristik Ceramic Coating Berpengikat Fosfat pada Baja Karbon Rendah - Dewi Idamayanti; Beny Bandanadjaja; Andreas Yosafat (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2019)
Low carbon steel is commonly used in the coal handling industry, but has low erosion and corrosion resistance. Hence, there is often a performance decrease due to the work environment that causes erosion and corrosion. Therefore, phosphate-bonded ceramic coating is applied. Al (OH) 3 and H3PO4 are used as a base material of binder. SiC (silicon carbide) and alumina are ceramic particles which is used in this research. The heat treatment was carried out for 1 hour, 3 hours and 5 hours to determine the effect of heat treatment time on phosphate bonded ceramic characteristics. The SEM results show that the longer of the heat treatment time, the more vacancies are formed. To determine erosion resistance of ceramic coating, erosion test is conducted, and the result show that erosion rate of ceramic coating with addition of SiC particles was 7.5 mg/Kg and without SiC was 14.2 mg/Kg. To make sure of berlinite, water resistance test was carried out, because berlinite is not soluble in water and will not lose mass significantly if it’s immersed in water. The losses obtained from the water resistance test were 0.074 %. The results of the overall characterization performed showed that the longer the heat treatment time, erosion resistance and water resistance increased in the span of 1 to 5 hours.